2019
DOI: 10.1002/adsc.201801262
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Unichiral Ligand‐Catalyzed Decarboxylative Asymmetric Protonation of Racemic β‐Oxoallyl Esters

Abstract: Scheme 9. DAPs leading to a-arylisoflavanones (R 1 ,R 2 ,R 3 ,R 4 = H, Me,OMe;R 2 -R 3 = CH 2 OCH 2 ).Scheme 10. DAPs leading to 7-(naphthalen-2-ylmethoxy)isoflavanones (R 1 ,R 2 ,R 3 ,R 4 = H, OMe,R 1 -R 2 = CHCH=CHCH). Scheme11. DAPs leading to a-aryloxindoles (R 1 ,R 2 ,R 3 , R 4 = H, Me,OMe;R 2 -R 3 = CH 2 OCH 2 ). Scheme 21. Guirysmechanistic proposal for the palladium-catalyzed DPAofa llyl b-keto esters with formic acid. Scheme 22. Plausible enantiodetermining transition state for the Meldrumsa cid-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…To date, several strategies have been employed for enantioselective protonation, including (a) protonation of enol ethers and enol esters by chiral proton donors, (b) protonation of enolates generated by chiral Brønsted base catalysts, and (c) protonation of Pd enolates by achiral Brønsted acids (Scheme 1). [1g,k,l] In the cases involving chiral proton catalysis, pre‐preparation of the enolate equivalents is typically required for activation of the carbonyl compounds. In contrast to these strategies, we envisioned a novel enantioselective protonation of in situ‐generated transient enolate equivalents.…”
Section: Methodsmentioning
confidence: 99%
“…To date, several strategies have been employed for enantioselective protonation, including (a) protonation of enol ethers and enol esters by chiral proton donors, (b) protonation of enolates generated by chiral Brønsted base catalysts, and (c) protonation of Pd enolates by achiral Brønsted acids (Scheme 1). [1g,k,l] In the cases involving chiral proton catalysis, pre‐preparation of the enolate equivalents is typically required for activation of the carbonyl compounds. In contrast to these strategies, we envisioned a novel enantioselective protonation of in situ‐generated transient enolate equivalents.…”
Section: Methodsmentioning
confidence: 99%
“…[49] To overcome these problems, transition-metal catalysts were employed in combination with mild oxidants. [50] In this context, Song et al reported the use of Pd/Cu-loaded POP for the heterogeneous oxidation of alkynes to 1,2-diketones using O 2 as the oxidant (Scheme 10). [51] A wide range of substituted alkynes with various functional groups were oxidized to their corresponding 1,2-diketones in high to excellent yields (76-99%).…”
Section: Hydroformylation Reactionsmentioning
confidence: 99%
“…Typically 1,2‐diketones are prepared by the oxidation of 1,2‐diaryl/alkyl‐alkynes using strong oxidants such as KMnO 4 , and organic peroxides, and these oxidants suffer from issues such as functional group tolerance, and waste disposal problems [49] . To overcome these problems, transition‐metal catalysts were employed in combination with mild oxidants [50] . In this context, Song et al .…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…22 Further work to expand the types of substrates for decarboxylative protonation has been since carried out and this has been reviewed extensively recently by Guiry 23 and Muzart. 24 Notably, independent mechanistic experiments have demonstrated that formic acid is not the sole proton source (Figure 2d). 22,25 Troubled by the lack of mechanistic understanding of the origin of the proton, as well as believing that there may be wider implications for the DcA field, we undertook a mechanistic study to attempt to determine the source of this atom.…”
Section: Figure 1 Pd-catalyzed Decarboxylative Allylation Reactions Yielding Allylation and Protonation Products With (A)β-keto Esters Ormentioning
confidence: 99%